Beijing comrades a novel - Xiao, He (The Feminist Press, 2016)
"When Handong, a ruthless and wealthy businessman, is introduced to Lan Yu, a naive, working-class architectural student-the attraction is all consuming. Arrogant and privileged, Handong is unsettled by this desire, while Lan Yu quietly submits. Despite divergent lives, the two men spend their nights together, establishing a deep connection. When loyalties are tested, Handong is left questioning his secrets, his choices, and his very identity. Beijing Comrades is the story of a torrid love affair set against the sociopolitical unrest of late-eighties China. Due to its depiction of gay sexuality and its critique of the totalitarian government, it was originally published anonymously on an underground gay website within mainland China. This riveting and heartbreaking novel, circulated throughout China in 1998, quickly developed a cult following, and remains a central work of queer literature from the People's Republic of China. This is the first English-language translation of Beijing Comrades. Bei Tong is the anonymous author of Beijing Comrades. The author's real-world identity has been a subject of ongoing debate since the novel was first published. Scott E. Myers is a translator of Chinese who focuses on contemporary queer fiction from the PRC. Petrus Liu is an associate professor of humanities at Yale-NUS College, Singapore"--
Keywords: Gay men / Fiction / China; FICTION / Gay; HISTORY / China / Asia; HISTORY / Modern / 20th Century; POLITICAL SCIENCE / Censorship; Gay men / China / Fiction; Asien